ANALISIS SIMULASI GELOMBANG HARMONISA DAN INSTALASI FILTER MENGGUNAKAN ETAP 12.6 PADA BUS PWI Di JOB Pertamina – Petrochina East Java Tuban - Agung Prasetyo; Agus Darwanto (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2020)
Harmonics are wave defects caused by interactions between the system's sinusoidal waves and other wave components that have integer multiples of their fundamental components. The cause of this harmonics is the presence of non-linear loads such as converters, electric arc furnaces, UPS and others that are not sinusoidal. Losses due to the influence of harmonics such as heating on the equipment, decreasing power factor, resonance problems etc. In this study the authors aim to analyze the level of harmonic THD contained in the PWI bus using simulation methods in order to obtain the harmonic THD percentage and the calculation method of capacitor components, inductors and resistor used for filter design to reduce the level of the harmonic THD percentage. The results of the discussion show that the THD voltage on the PWI bus exceeds the IEEE 519-2014 standard limit of 9.29% with the IEEE 519-2014 THD voltage of 8%, while for the THD the current despite increasing percentage after installation of a single tuned filter, with a percentage an increase of 0.96% from 8.65% to 9.61% on PWI buses, but the percentage increase in current THD is still below the IEEE 519-2014 standard with a current THD standard value of 15%.